Terminologies, modèles de données archéologiques et thésaurus documentaires : réflexions à partir d’une typologie de céramiques - Sébastien Durost; Guillaume Reich; Jean-Pierre Girard (Humanités Numériques)
The HyperThesau and Bibracte numérique projects have given rise to a collective effort centred on the use of vocabulary as a means of ensuring the interoperability of archaeological data throughout their life cycle. To this end, the use of the standardised form of the thesaurus – via the Opentheso platform – provides a tool that is already adapted to linked data. Nevertheless, its use quickly raised the question of the different paradigms presiding over the elaboration of a specific vocabulary by each (group of) scientist(s). The ISO 25964 standard – designed for the management and interoperability of indexing languages – is flexible enough to permit the comparison and linking of different scientific or documentary “points of view”. Their coherence through interoperability alignments nevertheless requires to interface different semantic granularities: search reporting, the description of raw data, a gateway or “pivot” between the two, by using a regulated cooperation methodology. The challenges that remain to be met on this path do not prevent the thesaurus tool from already being a suitable support for a complete “human-to-machine-to-human” interoperability, developed within the framework of the Bibracte ville ouverte project and exemplified through a published research on the ceramics of that archaeological site.